GE_GERICHTE P/4263/2025 vom 19. März 2025 - GE Cour de justice (2025)
DÉFENSE OBLIGATOIRE;AUDITION OU INTERROGATOIRE;POLICE;MESURE DE CONTRAINTE(PROCÉDURE PÉNALE);PREUVE | CPP.141; CPP.158; CPP.142; CPP.131